2019
DOI: 10.1017/pasa.2019.30
|View full text |Cite
|
Sign up to set email alerts
|

The emission and scintillation properties of RRAT J2325−0530 at 154 MHz and 1.4 GHz

Abstract: Rotating Radio Transients (RRATs) represent a relatively new class of pulsar, primarily characterised by their sporadic bursting emission of single pulses on time scales of minutes to hours. In addition to the difficulty involved in detecting these objects, low-frequency (< 300 MHz) observations of RRATs are sparse, which makes understanding their broadband emission properties in the context of the normal pulsar population problematic. Here, we present the simultaneous detection of RRAT J2325−0530 using the Mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 97 publications
3
13
0
Order By: Relevance
“…Earlier in Logvinenko (2020), RRATs have already been noted, in which the average time between pulses exceeded 10 hours. It is known that the appearance of RRAT pulses can obey the Poisson distribution (Meyers, 2019). In the paper Smirnova (2022) it was shown that the distribution of nullings (i.e., the duration of intervals without pulses) for some RRATs obeys an exponential law.…”
Section: Discussion Of Results and Conclusionmentioning
confidence: 99%
“…Earlier in Logvinenko (2020), RRATs have already been noted, in which the average time between pulses exceeded 10 hours. It is known that the appearance of RRAT pulses can obey the Poisson distribution (Meyers, 2019). In the paper Smirnova (2022) it was shown that the distribution of nullings (i.e., the duration of intervals without pulses) for some RRATs obeys an exponential law.…”
Section: Discussion Of Results and Conclusionmentioning
confidence: 99%
“…There is only one investigation with simultaneous observations RRAT at meter and decimeter wavelength (Meyers, 2019). They find that the single-pulse amplitude distribution is a truncated exponential at 150 MHz and a power low at 1400 MHz.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of the pulse amplitude distribution in more than two dozen RRATs discovered in the decimeter wavelength range (Cui et al, 2017, Mickaliger, 2018, Shapiro-Albert, 2018 showed a lognormal or lognormal with power law tail distribution. Meyers (2019) estimated the pulse energy distribution for J2325-0530 at 150 MHz and 1400 MHz but because of small sample of single pulses they were unable to drow concrete conclusions. Since our sample is small and does not have observations at higher frequences, it is impossible to conclude that the distribution of the pulse amplitude may depend on the frequency of observations for all RRATs.…”
Section: Discussionmentioning
confidence: 99%
“…giant pulses), or switching emission states (e.g. Kramer et al 2006a;Lorimer et al 2012;Young et al, 2014;Meyers et al 2017Meyers et al , 2018Meyers et al , 2019. Such emission occurs on timescales of seconds to months, and the pulsars which exhibit such types of emission pose a major challenge to our understanding of the underlying physics that govern the radio emission mechanism.…”
Section: Sporadic and Intermittent Emissionmentioning
confidence: 99%